Code-switching for non-native Korean lecturers in teaching Korean as a foreign language for basic and additional level - Sari Tiana Arti Nurani (Journal of Korean Applied Linguistics, 2022)
Although communication is a means of exchanging ideas between people, it can be challenging due to the abundance of synonyms and the evolution of language. The idea is that rather than code-switching, each person needs to have the aptitude and competence to comprehend different kinds of language. This study focuses on the use of code-switching by lecturers in the learning process. The purpose of this study was to find out what types of code-switching were used by lecturers during the learning process, what was the function of using code-switching, and how students perceived the use of code-switching by lecturers in learning activities. This research is based on the awareness that the ability of students to capture learning in the classroom varies. This research is expected to help Korean language learning effectively. The method used in this research was descriptive qualitative, with one lecturer and 71 students as respondents. Data in the form of a transcription of the lecturer’s speeches were obtained from four learning video documentation and questionnaires. Three types of code-switching were found in the lecturer's speech at each meeting, namely the tag-switching type, the intra-sentential-switching, and the intersentential-switching. Then there were five functions realized at each meeting, namely referential functions, emotive functions, conative functions, fatigue functions, and metalinguistic functions. Students’ responses to the lecturer’s code-switching, as evidenced in the questionnaires, were generally positive, especially in terms of understanding the materials.